Image retrieval based on Multi Expression Programming algorithms - Wang, Weihong; Lin, Wenrou; Li, Qu (Proceedings (International Conference on Natural Computation. Print), 2013)
The effectiveness of content-based image retrieval (CBIR) systems can be improved by combining image features or by weighting image similarities, as computed from multiple feature vectors. However, feature combination does not always make sense and the combined similarity function can be more complex than weight-based functions to better satisfy the users' expectations. This paper addressed this problem by presenting a Multi-Expression Programming (MEP) framework to design combined similarity functions. This method allows nonlinear combination of image similarities and is validated through experiments, where the images are retrieved based on the shape of their objects. Experimental results demonstrate that the MEP framework is suitable for the design of effective combinations functions.